Malondialdehyde level in the lens of complicated cataract patients with the instillation of diclofenac sodium 0,1% eye drop pre-operatively - Wiwik Widowati Wiwik Widowati (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2004)
Objective: To determine the level of malonaldehyde of lens in complicated cataract patients receiving instillation of diclofenac sodium 0,1% eye drop, 3 times daily, 2 weeks before undergoing surgery. Materials and methods: A cross sectional study on complicated cataract patients who underwent extracapsular cataract extraction, was conducted at Dr. Sardjito General Hospital, dr. Yap Eye Hospital and mass cataract surgery in Yogyakarta and surrounding area, from November 2002 until November 2003. Subjects were consecutively recruited and classified into two groups. Twenty patients received diclofenac sodium 0,1% eye drop 3 times daily for two weeks before lens extraction, and 20 patients who received no treatment served as control. On the day of surgery, the lens was taken to measure the level of MDA at the Laboratory of Biochemistry. The difference of MDA level between the two groups was statistically analyzed by student t test.Results: The mean MDA level in the group receiving diclofenac sodium was 4,386 Â± 2,625 nmol/g, while in the group without diclofenac sodium it was 6,728 Â± 3,422 nmol/g. This difference was statistically significant with p = 0.020.Conclusion: The mean MDA level in diclofenac sodium group was lower than that without diclofenac sodium group.Key words: malondialdehyde level - caractogenesis - complicated cataract - diclofenac sodium.